PELATIHAN PENINGKATAN KOMPETENSI TENAGA KEPENDIDIKAN DI SEKOLAH MENENGAH ATAS NEGERI 8 BATANG HARI PROVINSI JAMBI - Sumiyani, Sumiyani; Safitri, Dini; Adila, Risti; Zuliana, Rizqi; Annisa, Siti; Miranti, Peni Alya; Sagita, Lilis (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
Training to improve the competence of educational personnel is a crucial effort to enhance the quality of educational services in schools. As part of the human resources in education, educational personnel play a strategic role in supporting teaching and learning activities, both in administrative and technical aspects. However, field observations show that many educational personnel still lack the necessary competencies in line with current demands and technological advancements. Therefore, well-structured and continuous training is essential to improve their professionalism. This training aims to strengthen the competencies of educational personnel in various areas, including educational administration management, the use of information technology in daily tasks, excellent service delivery for the school community, and the reinforcement of work ethics and discipline. The training methods used include participatory approaches, group discussions, case studies, and real-work simulations, allowing participants to not only understand the theory but also practice it in their respective work environments. The results of the training indicate significant improvement in participants' ability to prepare administrative documents, operate supporting software, and their awareness of ethical behavior and friendly service. This training also fosters collaborative spirit among educational personnel, creating a more harmonious and productive working environment. Overall, this training has a positive impact on improving the performance of educational personnel and is expected to become part of a continuous human resource development program in schools. With well-targeted training, educational personnel can become professional partners who contribute to the overall improvement of education quality. ABSTRAK Pelatihan peningkatan kompetensi bagi tenaga kependidikan merupakan langkah penting dalam rangka meningkatkan mutu layanan pendidikan di sekolah. Tenaga kependidikan sebagai bagian dari sumber daya manusia pendidikan memiliki peran strategis dalam mendukung kegiatan belajar mengajar, baik dalam aspek administratif maupun teknis. Namun, kenyataan di lapangan menunjukkan bahwa masih banyak tenaga kependidikan yang belum memiliki kompetensi yang memadai sesuai dengan tuntutan perkembangan zaman dan teknologi. Oleh karena itu, pelatihan yang terstruktur dan berkelanjutan menjadi kebutuhan mutlak untuk meningkatkan profesionalisme mereka. Tujuan dari kegiatan ini adalah memberikan penguatan kompetensi tenaga kependidikan dalam beberapa aspek, antara lain: manajemen administrasi pendidikan, pemanfaatan teknologi informasi dalam pekerjaan, pelayanan prima terhadap warga sekolah, serta penguatan etika dan kedisiplinan kerja. Metode pelatihan yang digunakan meliputi pendekatan partisipatif, diskusi kelompok, studi kasus, dan simulasi kerja nyata, sehingga peserta tidak hanya memahami secara teoritis tetapi juga mampu menerapkannya dalam lingkungan kerja masing-masing. Hasil dari pelatihan menunjukkan adanya peningkatan kemampuan dalam menyusun dokumen administrasi, mengoperasikan perangkat lunak penunjang tugas, serta meningkatnya kesadaran akan pentingnya etika kerja dan pelayanan yang ramah. Pelatihan ini juga berhasil mendorong semangat kolaboratif antar tenaga kependidikan, menciptakan lingkungan kerja yang lebih harmonis dan produktif. Secara keseluruhan, pelatihan ini berdampak positif terhadap peningkatan kinerja tenaga kependidikan dan diharapkan menjadi bagian dari program pengembangan sumber daya manusia secara berkelanjutan di sekolah. Melalui pelatihan yang tepat sasaran, tenaga kependidikan mampu menjadi mitra profesional yang mendukung peningkatan kualitas pendidikan secara menyeluruh.